67.0k views
1 vote
If
B is the midpoint of AC, AB=x+6 and AC=5x-6, then what is BC?

User CocoCrisp
by
5.0k points

1 Answer

5 votes

If B is the midpoint of AC, then AB=BC. It is also BC=AC-AB

AB = x + 6

AC = 5x - 6

BC = (5x - 6) - (x + 6)

We can kinda use distributive property, like this:

BC = 5x - 6 -x - 6

Combine like terms:

BC = 4x - 12

To verify, we can add AB and BC to see if their sum is equal to AC.

(x + 6) + (4x - 12) = 5x - 6

If we are correct, this equation will be true.

x + 6 + 4x - 12 = 5x - 6

Combine like terms:

6 + 5x - 12 = 5x - 6

5x - 6 = 5x - 6

It's correct!

BC = 4x - 12. Final Answer.

Let me know if you have any questions about this! :)

User Mychelle
by
5.8k points